Answer:
The answer to your question is the second option 
Step-by-step explanation:
Expression
![[\frac{(x^{2}y^{3})^{-2}}{(x^{6}y^{3}z)^{2}}]^{3}](https://tex.z-dn.net/?f=%5B%5Cfrac%7B%28x%5E%7B2%7Dy%5E%7B3%7D%29%5E%7B-2%7D%7D%7B%28x%5E%7B6%7Dy%5E%7B3%7Dz%29%5E%7B2%7D%7D%5D%5E%7B3%7D)
Process
1.- Divide the fraction in numerator and denominator
a) Numerator
[(x²y³)⁻²]³ = (x⁻⁴y⁻⁶)³ = x⁻¹²y⁻¹⁸
b) Denominator
[(x⁶y³z)²]²= (x¹²y⁶z²)³ = x³⁶y¹⁸z⁶
2.- Simplify like terms
a) x⁻¹²x⁻³⁶ = x⁻⁴⁸
b) y⁻¹⁸y⁻¹⁸= y⁻³⁶
c) z⁻⁶
3.- Write the fraction

<span>Simplifying
4x = 92
Solving
4x = 92
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Divide each side by '4'.
x = 23
Simplifying
x = 23</span>
Answer:
46
Step-by-step explanation:
230 divided by 5
Answer:
A,D,C would be your answers
Step-by-step explanation:
Answer:
1875.6 in³
Step-by-step explanation:
(⅓×3.14×8²×12) + (⅔×3.14×8³)
1875.626667 in³